Hubungan Kemampuan Kontrol Diri dengan Kecenderungan Depresi pada Mahasiswa Program B PSIK Fk UGM - Ni Wayan Wiwin Asthiningsih, Carla R. Marchira, Mariyono Sedyowinarso (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: The failure of the individual in adjusting to the demands of the problem or will make their lives are in stressful situations and disturbing emotions that will cause the individual response to these pressures. Individual response to a stressful situation depends on their control of the situation. This is usually called the locus of control. There are two types of locus of control in humans, namely internal locus of control and external locus of control. Individuals who possess an internal self-control, then the stress levels experienced lower so that the tendency to be a little depressed. The individual who has control of the external self, the stress levels experienced higher so that the tendency to experience depression will also be greater.Objectives: To determine the relationship between the ability of self control (locus of control) with a tendency to depression in student program B PSIK FK UGM.Methods: This study uses the method of non-experimental research with crosss sectional research design, using quantitative methods and descriptive correlation. To find relationships between variables using Pearson Product Moment correlation. Respondent of this study was students of program B PSIK FK UGM 2009/2010 school year.Results: Out of 78 respondents indicated that locus of control most widely owned by students program B PSIK FK UGM is internal locus of control that is 80.8%. In addition the research also found no depression was 82.1%, mild depression was 12.8%, and depression was 5.1%. The relationship between the ability of locus of control with a tendency to depression in student program B PSIK FK UGM was showed with value of r = 0.702 (p=0.001).Conclusion: There was signif icant relationship between the ability of locus of control with tendency to depression in student program B PSIK FK UGM.Keywords: locus of control, depression, PSIK students